White Box Implementations of Dedicated Ciphers on the ARM NEON Architecture - Dahab, Ricardo; López, Julio; Rodrigues, Félix Carvalho; Fujii, Hayato; Sider, Giuliano; Serpa, Ana Clara (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2018)
Modern computer environments such as smartphones are increasingly susceptible to malware, a cause of concern regarding their trustworthiness. Nevertheless, cryptographic algorithms are still necessary in such environments, which raises the need for a secure white-box design and implementation of such algorithms. Dedicated white box block ciphers are encryption algorithms designed to operate in untrusted environments. In this paper we present a fast vectorized implementation of two families of dedicated white-box block ciphers, SPACE [Bogdanov and Isobe 2015] and WEM [Cho et al. 2017], for the ARM Cortex-53 processor, using the NEON vector instruction set. To the best of our knowledge, the implementations outlined in this paper currently have the best reported performance for these dedicated ciphers in the white box context.